Effect of chronic Giardia lamblia infection on epithelial transport and barrier function in human duodenum. Issue 3 (25th August 2006) - Troeger, Hanno; Epple, Hans-Joerg; Schneider, Thomas; Wahnschaffe, Ulrich; Ullrich, Reiner; Burchard, Gerd-Dieter; Jelinek, Tomas; Zeitz, Martin; Fromm, Michael; Schulzke, Joerg-Dieter
Abstract : Background: Giardia lamblia causes infection of the small intestine, which leads to malabsorption and chronic diarrhoea. Aim: To characterise the inherent pathomechanisms of G lamblia infection. Methods: Duodenal biopsy specimens from 13 patients with chronic giardiasis and from controls were obtained endoscopically. Short-circuit current (ISC ) and mannitol fluxes were measured in miniaturised Ussing chambers. Epithelial and subepithelial resistances were determined by impedance spectroscopy. Mucosal morphometry was performed and tight junction proteins were characterised by immunoblotting. Apoptotic ratio was determined by terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labelling staining. Results: In giardiasis, mucosal surface area per unit serosa area was decreased to 75% (3%) of control, as a result of which epithelial resistance should increase. Instead, epithelial resistance of giardiasis biopsy specimens was decreased (19 (2) vs 25 (2) Ω cm 2 ; p<0.05) whereas mannitol flux was not significantly altered (140 (27) vs 105 (16) nmol/h/cm 2 ). As structural correlate, reduced claudin 1 expression and increased epithelial apoptosis were detected. Furthermore, basal ISC increased from 191 (20) in control to 261 (12) µA/h/cm 2 in giardiasis. The bumetanide-sensitive portion of ISC in giardiasis was also increased (51 (5) vs 20 (9) µA/h/cm 2 in control; p<0.05). Finally, phlorizin-sensitive Na + –glucose symport was reduced in patients with giardiasis (121 (9) vs 83 (14) µA/h/cm 2 ). Conclusions: G lamblia infection causes epithelial barrier dysfunction owing to down regulation of the tight junction protein claudin 1 and increased epithelial apoptoses. Na + -dependent d -glucose absorption is impaired and active electrogenic anion secretion is activated. Thus, the mechanisms of diarrhoea in human chronic giardiasis comprise leak flux, malabsorptive and secretory components.